Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Hasil Belajar Mata Pelajaran Bahasa Indonesia : Application of Jigsaw Type Cooperative Learning Model to Improve Learning Outcomes of Indonesian Subjects - Atiyani, Atiyani (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to improve Indonesian language learning outcomes in fourth grade students of SDN Megamendung 03 through the application of the Jigsaw type cooperative learning model. Using a Classroom Action Research (PTK) approach with two cycles, the research was conducted on 18 students (10 boys and 8 girls) in the even semester of the 2019/2020 academic year. The results showed an increase in the average value of student learning outcomes from 60.2 in cycle I to 75.6 in cycle II, with an increase of 15.4. The percentage of learning completeness increased from 39% to 89%. Changes in student behavior in the aspects of activeness, cooperation, and participation also increased from an average score of 65 in cycle I to 94 in cycle II. These results prove that the application of the Jigsaw type cooperative learning model is effective in improving students' learning outcomes and activities in Indonesian language learning.